A study of constitutional supremacy in Malaysia - Hamid, Noor ‘Ashikin; Salleh, Kamaliah; Harun, Noraida; Bidin, Asiah; Ismail @ Nawang, Nazli (Universiti Teknologi MARA, Kelantan, 2018)
The concept of constitutional supremacy is provided by Article 4 (1) and 162(6) of the Malaysian Federal Constitution. It is differed from the doctrine of supremacy of Parliament as practised in English jurisprudence. The objective of this paper is to study the concept of constitutional supremacy, why it has become very important and the dangers that it poses if there is erosion of the concept. The study is based on doctrinal research as it is primarily concerned with the review of the provisions of the Constitution and reported cases that have been decided by the local courts. It is suggested that it was possible for Parliament to amend the Constitution to a point where it basically may defect the concept of constitutional supremacy in Malaysia.